The Methuen Drama guide to contemporary British playwrights: Landmark playwrights from 1980 to the present - Middeke, Martin; Schnierer, Peter Paul; Sierz, Aleks (Bloomsbury Publishing, 2011)
This is an authoritative single-volume guide to the work of twenty-five British playwrights from the 1980s to the present written by an international team of twenty-five eminent scholars. It is the perfect companion for students of Theatre Studies and English Literature
Includes index. - Print version record
Keywords: Electronic books; Electronic books -- Criticism, interpretation, etc; Wörterbuch; Biografie; Drama; Englisch; Geschichte 1980-2010; Dramatiker; Großbritannien